Effects of porosity on dynamic indentation resistance of silica nanofoam. Issue 1 (December 2017) - Zhao, Cang; Zhong, Ying; Qiao, Yu
Abstract The dynamic indentation behaviors of monolithic silica nanofoams of various porosities are investigated. When the pore size is on the nm scale, as the porosity increases, despite the decrease in mass density, the resistance offered by silica nanofoam to dynamic indentation is maintained at a high level, higher than the resistance of solid silica or regular porous silica. This phenomenon is related to the fast collapse of nanocells, which produces a locally hardened region and significantly increases the volume of material involved in impact energy dissipation.